Hubungan Karakteristik Petani dengan Tingkat Adopsi Inovasi Pembuatan Bokashi dari Limbah Ternak Sapi - Shalma Alifia Rosyida; Budi Sawitri; Dwi Purnomo (Fakultas Pertanian Universitas Jember, 2021)
This study aims to analyse the relationship between farmers characteristics and the level of adoption innovation in making bokashi fertilizer from cow waste in Cukurgondang village Grati subdistict Pasuruan regency. This study was conducted in Cukurgondang village Grati subdistict Pasuruan regency. The study’s method using survey methods with quantitative descriptive data analysis. Sample determination according Arikunto (2012) that samples are 25% from population. Determination of sample use Simple Random Sampling technique and sampling of this study are 49 people. Independent variable is farmer’s characteristics (include age, formal education, nonformal education, experience, land area and income) and the dependent variable is the adoption innovation in making bokashi fertilizer from cow waste. Data analysis using Spearman Rank correlation test to determine the relationship between farmers characteristics and the level of farmers adoption in making bokashi fertilizer from cow waste. The result showed that the level of adoption innovation in making bokashi fertilizer from cow waste in Cukurgondang village Grati subdistict Pasuruan regency is low. Farmers characteristics which have significant related to the adoption in making bokashi fertilizer from cow waste are age, formal education, nonformal education and experience. Keywords: Adoption, Inovation, Farmer characteristics, Bokashi fertilizer